RUNNING DYNAMICS IN MALE 400M SPRINT EVENT - D. GRGIĆ; V. BABIC; I. BLAŽEVIĆ 3 (Editura Universitatii Transilvania din Brasov, 2019)
The main goal of this research was to determine the running dynamics in male 400m sprint event. This research was conducted on top male athletes who progressed into the finals of four World Championships in athletics: Stuttgart (1993), Athens (1997) Seville (1999) and Berlin (2009). The data for this study was taken from the list of official results and published biomechanical analysis. This research study included 15 variables; 14 of which were time parameters referring to split times at every 50m, at every 100m and at first and last 200m in 400m event, as well as final result, sprinters' age, height and weight. Obtained results were then used to determine basic statistical parameters as well as to determine individual changes in running dynamics of 400m race. Obtained results show miniscule differences in 400m running dynamics that impact better final placement considering the successfulness of movement structure patterns realization.